Freeze and Thaw of CD4+CD25+Foxp3+ Regulatory T Cells Results in Loss of CD62L Expression and a Reduced Capacity to Protect against Graft-versus-Host Disease. - Mareike Florek; Dominik Schneidawind; Antonio Pierini; Jeanette Baker; Randall Armstrong; Yuqiong Pan; Dennis Leveson-Gower; Robert Negrin; Everett Meyer (PLoS ONE)
The adoptive transfer of CD4+CD25+Foxp3+ regulatory T cells (Tregs) in murine models of allogeneic hematopoietic cell transplantation (HCT) has been shown to protect recipient mice from lethal acute graft-versus-host disease (GVHD) and this approach is being actively investigated in human clinical trials. Here, we examined the effects of cryopreservation on Tregs. We found that freeze and thaw of murine and human Tregs is associated with reduced expression of L-selectin (CD62L), which was previously established to be an important factor that contributes to the in vivo protective effects of Tregs. Frozen and thawed murine Tregs showed a reduced capacity to bind to the CD62L binding partner MADCAM1 in vitro as well as an impaired homing to secondary lymphoid organs in vivo. Upon adoptive transfer frozen and thawed Tregs failed to protect against lethal GVHD compared with fresh Tregs in a murine model of allogeneic HCT across major histocompatibility barriers. In summary, the direct administration of adoptively transferred frozen and thawed Tregs adversely affects their immunosuppressive potential which is an important factor to consider in the clinical implementation of Treg immunotherapies.